Pesquisaje de pesticidas organoclorados contaminantes de embalses - Acosta, A.=700 1 Sanchez, N.
(En, Es)
Ilus., 16 ref.
Keywords: TILAPIA; OREOCHROMIS NILOTICUS; PLAGUICIDAS; DIELDRIN; COMPUESTO ORGANICO DEL CLORO; POLUCION DEL AGUA; EMBALSES; TOXICIDAD; CUBA; PESTICIDAS ORGANOCLORADOS